Analisis Faktor-Faktor Penentu Harga Pokok Pengolahan Produksi Di Pabrik Kelapa Sawit Sei Silau PTPN IV Regional 1 Palmco - Sihaloho, Leo Frengki; Lubis, Zulkarnain; Sibuea, Buhari (JURNAL AGRICA, 2025)
Oil palm (Elaeis guineesis Jacq.) is an annual plant that plays an important role and oil palm is Indonesia's leading and main agricultural commodity or is often referred to as Indonesia's green jewel. Indonesia is the largest producer and exporter of CPO in the world to meet domestic and foreign needs, followed by Malaysia, Thailand, Nigeria, Colombia and Papua New Guinea. Even though Indonesia has indeed succeeded in becoming the largest CPO producer in the world, the reality shows that Indonesia has not been able to determine theselling price of CPO for the world market. It is not only the issue of market integration that is still determined by foreign markets. Therefore, private and state-owned palm oil factories usually calculate the cost of production using the processing cost method and analyze what factors influence the cost of production. For this reason, private and state-owned palm oil factories usually calculate the cost of production using the processing cost method  and analyze what factors influence the cost of production. The main objective of this research is to determine the influence of processing capacity, raw material supplies, oil and palm kernel oil yields and exploitation costs on the cost of processing so that it can provide added value for the company. This research uses secondary data and is analyzed using linear regression using SPSS. Based on the research results, it is known that processing capacity has no effect on the cost of processing and this is not in accordance with the hypothesis. Raw material supplies and yield achievements have a negative and significant effect on the cost of processing goods and are in accordance with the hypothesis. Exploitation costs have a positive and significant effect on the cost of processing and are in accordance with the hypothesis. Therefore, management must increase raw material supplies and production yields and reduce exploitation costs to reduce the cost of processing goods.